Risk-benefit perception and intention to vote in favor of bicycle lanes - Limón-Domínguez, Gerardo Arturo; Valdés-Ambrosio, Oscar; Molina-Ruíz, Héctor Daniel; Rivera-Varela, Bertha Leticia; García-Lirios, Cruz (Tendencias Sociales. Revista de Sociología, 2019)
Within the framework of policies against the effects of climate change on public health, mobility policies based on zero carbon dioxide emissions have focused their interest on the implementation of bicycle lanes, the subsidy of bicycle engines and restriction of automobiles. In this sense, the objective of this paper has been to establish the reliability and validity of an instrument that measures the perceptions of risk and utility, as well as the intentions of voting in favor of electoral proposals and candidates that support the urban sustainability policy in Subject d mobility. A non-experimental, cross-sectional and exploratory study was carried out with a non-probabilistic sample selection of 250 residents of the metropolitan area of Mexico City. From a structural model. The factors cited were found to correlate positively and significantly, but it is recommended to extend the study to the contrast of the model in other scenarios with local elections and mobility policy based on the use of the bicycle